Analisis Kebutuhan Pengembangan Booklet Terintegrasi Etnosains pada Materi Ekosistem SMA - Sri Amanda; Fitri Olvia Rahmi (LP2M UIN Ambon, 2026)
Teaching materials are an important component that serve as a learning resource for educators and students. The purpose of this study is to describe the results of a needs analysis for the development of an integrated ethoscience booklet on high school ecosystem material. The research data were collected using instruments for a preliminary study, consisting of interview sheets for biology teachers and a needs analysis questionnaire administered to 30 students in Class X Phase E at Tilatang Kamang State High School 2. The data were analyzed using descriptive qualitative and quantitative methods. The results indicate that students need supplementary teaching materials that are engaging, easy to understand, and contextual. Furthermore, the interview results reveal that the integration of ethnoscience into learning is not yet supported by adequate teaching materials. Therefore, the development of an integrated ethnoscience booklet is necessary as an alternative teaching resource that meets the needs of both teachers and students.